# The Chain Rule in Leibniz Notation Exercises

### Example 1

*z*=*ln*(*x*^{5}+ 4*x*^{2})

### Example 2

*z*= (sin*x*+ cos*x*)^{7}

### Example 3

### Example 4

*z*= e^{{12x + 4}}

### Example 5

### Example 6

For the pair of functions, determine what the chain rule says.

- Let
*p*=*f*(*s*) and*s*=*g*(*z*).

### Example 7

For the pair of functions, determine what the chain rule says.

- Let r =
*g*(*t*) and*q*=*f*(*r*).

### Example 8

For the pair of functions, determine what the chain rule says.

- Let
*x*=*f*(*y*) and*y*=*g*(*z*).

### Example 9

- If
*u*= e^{s}and*s*= 5 - 3*x*^{2}, find .

### Example 10

- If
*s*=*t*^{4}and*t*=*r*^{4}+ 1, find .

### Example 11

- If
*m*= sin*n*and*z*=*ln**m*, find .

### Example 12

- If
*z*= (*x*^{4}+ 4*x*) and*y*=*z*^{3}+*z*^{5}, find .

### Example 13

- If and
*q*= tan*p*, find .

### Example 14

- Find given that
*r*= sin(*x*^{2}+ 1) + cos(*x*^{2}+ 1).

### Example 15

- Find given that
*p*= e^{{r2 + 3r}}

### Example 16

- Find given that
*y*=*ln*(*z*^{4}+*z*^{3})

### Example 17

- Find given that

### Example 18

- Find given that
*q*= 14^{{12sin t}}.